A Study of the Relationship between Digital Leadership of School Administrators and Promotion of Teacher’s Innovative Thinking Skills under Phitsanulok Primary Educational Service Area Office 3 - Saewa, Narapat; Wechayaluck, Nirada (Ratchaphruek Journal, 2024)
The purposes of this research were to: 1) study the digital leadership of school administrators, 2) study the promotion of teachers’ innovative thinking skills, and 3) examine the relationship between the digital leadership of school administrators and the promotion of teachers’ innovative thinking skills under Phitsanulok Primary Educational Service Area Office 3. The sample consisted of 113 schools under Phitsanulok Primary Educational Service Area Office 3, selected using Krejcie and Morgan’s table. The sample was taken using a stratified sampling method, identifying groups of informants, namely 113 school administrators and 113 teachers in educational institutions through random sampling. The research tool was a questionnaire using a 5-point Likert scale, with reliability coefficients of 0.98 for part 1 and 0.99 for part 2. The statistics used in the data analysis were mean, standard deviation, and Pearson’s correlation coefficient. The results of the study found that: 1) Digital leadership, in general, was at the highest level, 2) the promotion of teachers’ innovative thinking skills, in general, was at the highest level, and 3) the relationship between the digital leadership of school administrators and the promotion of teachers’ innovative thinking skills was at a moderate level of correlation, statistically significant at the .01 level.